Developmental roles of Auxin Binding Protein 1 in Arabidopsis thaliana - Gelová, Zuzana; Gallei, Michelle; Pernisová, Markéta; Brunoud, Géraldine; Zhang, Xixi; Glanc, Matouš; Li, Lanxin; Michalko, Jaroslav; Pavlovičová, Zlata; Verstraeten, Inge; Han, Huibin; Hajný, Jakub; et al. (Plant science, 2021)
Auxin is a major plant growth regulator, but current models on auxin perception and signaling cannot explain the whole plethora of auxin effects, in particular those associated with rapid responses. A possible candidate for a component of additional auxin perception mechanisms is the AUXIN BINDING PROTEIN 1 (ABP1), whose function in planta remains unclear. Here we combined expression analysis with gain- and loss-of-function approaches to analyze the role of ABP1 in plant development. ABP1 shows a broad expression largely overlapping with, but not regulated by, transcriptional auxin response activity. Furthermore, ABP1 activity is not essential for the transcriptional auxin signaling. Genetic in planta analysis revealed that abp1 loss-of-function mutants show largely normal development with minor defects in bolting. On the other hand, ABP1 gain-of-function alleles show a broad range of growth and developmental defects, including root and hypocotyl growth and bending, lateral root and leaf development, bolting, as well as response to heat stress. At the cellular level, ABP1 gain-of-function leads to impaired auxin effect on PIN polar distribution and affects BFA-sensitive PIN intracellular aggregation. The gain-of-function analysis suggests a broad, but still mechanistically unclear involvement of ABP1 in plant development, possibly masked in abp1 loss-of-function mutants by a functional redundancy.
Keywords: kyseliny indoloctové; proteiny huseníčku; Microscopy, Confocal; Hypocotyl; Plant Growth Regulators; Auxin; konfokální mikroskopie; Arabidopsis Proteins; regulace genové exprese u rostlin; Gene Expression Regulation, Plant; receptory buněčného povrchu; Protoplasts; Arabidopsis; regulátory růstu rostlin; hypokotyl; kořeny rostlin; Receptors, Cell Surface; rostlinné proteiny; Auxin signaling; Plant Proteins; Real-Time Polymerase Chain Reaction; protoplasty; Indoleacetic Acids; Plant Roots; Plant development; kvantitativní polymerázová řetězová reakce; AUXIN BINDING PROTEIN 1 (ABP1)